Effects of Mindfulness Based Cognitive Therapy (MBCT) and Compassion Focused Therapy (CFT) on Symptom Change, Mindfulness, Self-Compassion, and Rumination in Clients With Depression, Anxiety, and Stress - Frostadottir, Anna Dora; Dorjee, Dusana (Frontiers in Psychology, 2019)
Objectives: Over the past decade there has been an increasing interest in exploring self-compassion as a related and complementary construct to mindfulness. Increases in self-compassion may predict clinical outcomes after MBCT and cultivation of compassion towards self and others is central to CFT. This pilot study compared the impact of MBCT applying implicit self-compassion instructions and CFT employing explicit self-compassion instructions on symptom change, mindfulness, self-compassion and rumination. Method: This non-randomised wait-list controlled study (N=58) with two intervention arms (MBCT N=20, CFT N=18, Control N=20) assessed the outcomes of clients with depression, anxiety and stress symptoms from before to after the interventions and at one month follow up (MBCT N=17, CFT N=13, Control N=13). Results: Both treatments resulted in significant increases in mindfulness and self-compassion and decreases in rumination, depression, anxiety and stress. Furthermore, MBCT enhanced mindfulness for people who were initially high in rumination, whereas CFT enhanced mindfulness across the board. Conclusion: The findings suggest that both MBCT and CFT, and hence implicit or explicit self-compassion instructions, produce similar clinical outcomes with CFT enhancing mindfulness regardless of client’s rumination level.